Endocannabinoids are Involved in Male Vertebrate Reproduction: Regulatory Mechanisms at Central and Gonadal Level - Bovolin, Patrizia; Cottone, Erika; Pomatto, Valentina; Fasano, Silvia; Pierantoni, Riccardo; Cobellis, Gilda; Meccariello, Rosaria (Frontiers in Endocrinology, 2014)
Endocannabinoids are natural lipids regulating a large array of physiological functions and behaviors in vertebrates. The endocannabinoid system is highly conserved in evolution and comprises several specific receptors (type-1 and type-2 cannabinoid receptors), their endogenous ligands (e.g. anandamide and 2-arachidonoylglycerol), and a number of biosynthetic and degradative enzymes. In the last few years, endocannabinoids have been described as critical signals in the control of male and female reproduction at multiple levels: centrally, by targeting hypothalamic Gonadotropin-Releasing-Hormone secreting neurons and pituitary, and locally, with direct effects on the gonads. These functions are supported by the extensive localization of cannabinoid receptors and endocannabinoid metabolic enzymes at different levels of the hypothalamic-pituitary-gonadal axis in mammals, as well as bonyfish and amphibians. In vivo and in vitro studies indicate that endocannabinoids centrally regulate gonadal functions by modulating the Gonadotropin Releasing Hormone-gonadotropin-steroid network through direct and indirect mechanisms. Several proofs of local endocannabinoid regulation have been found in the testis and male genital tracts, since endocannabinoids control Sertoli and Leydig cells activity, germ cell progression, as well as the acquisition of sperm functions. A comparative approach usually is a key step in the study of physiological events leading to the building of a general model. Thus, in this review we summarize the action of endocannabinoids at different levels of the male reproductive axis, with special emphasis, where appropriate, on data from non-mammalian vertebrates.